Dietary restriction decreases coenzyme Q and ubiquinol potentially via changes in gene expression in the model organism C. elegans. (2nd May 2015) - Fischer, Alexandra; Klapper, Maja; Onur, Simone; Menke, Thomas; Niklowitz, Petra; Döring, Frank
Abstract Dietary restriction (DR) is a robust intervention that extends both health span and life span in many organisms. Ubiquinol and ubiquinone represent the reduced and oxidized forms of coenzyme Q (CoQ). CoQ plays a central role in energy metabolism and functions in several cellular processes including gene expression. Here we used the model organism Caenorhabditis elegans to determine level and redox state of CoQ and expression of genes in response to DR. We found that DR down‐regulates the steady‐state expression levels of several evolutionary conserved genes (i.e. coq‐1) that encode key enzymes of the mevalonate and CoQ‐synthesizing pathways. In line with this, DR decreases the levels of total CoQ and ubiquinol. This CoQ‐reducing effect of DR is obvious in adult worms but not in L4 larvae and is also evident in the eat‐2 mutant, a genetic model of DR. In conclusion, we propose that DR reduces the level of CoQ and ubiquinol via gene expression in the model organism C. elegans. © 2015 BioFactors, 41(3):166–174, 2015